The comparison of engine performance and exhaust emission characteristics of sesame oil-diesel fuel mixture with diesel fuel in a direct injection diesel engine - Altun, Sehmus; Bulut, Husamettin; Oner, Cengiz (Pergamon-Elsevier Science Ltd, 2008)
The use of vegetable oils as a fuel in diesel engines causes some problems due to their high viscosity compared with conventional diesel fuel. Various techniques and methods are used to solve the problems resulting from high viscosity. One of these techniques is fuel blending. In this study, a blend of 50% sesame oil and 50% diesel fuel was used as an alternative fuel in a direct injection diesel engine. Engine performance and exhaust emissions were investigated and compared with the ordinary diesel fuel in a diesel engine. The experimental results show that the engine power and torque of the mixture of sesame oil-diesel fuel are close to the values obtained from diesel fuel and the amounts of exhaust emissions are lower than those of diesel fuel. Hence, it is seen that blend of sesame oil and diesel fuel can be used as an alternative fuel successfully in a diesel engine without any modification and also it is an environmental friendly fuel in terms of emission parameters. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: sesame oil; alternative fuel; exhausts emissions; diesel engine; engine performance